TDP-43-proteinopathy at the crossroads of tauopathy: on copathology and current and prospective biomarkers - Nasir, Abdul R.; Delpirou Nouh, Claire (Frontiers in Cellular Neuroscience, 2025)
Though usually described as isolated models, neurodegenerative diseases exist in a significant proportion of cases as mixed pathologies, particularly in older adults. The presence of co-pathologies may influence phenotypes and progression, and the correct classification in vivo has proven to be challenging, particularly without proper biomarker panels. Recent breakthroughs in biomarkers, enabling earlier detection in Alzheimer’s disease and, more recently, in synuclein-related diseases, are promising as a first step toward the wider detection of all other abnormal proteins involved in neurodegenerative diseases. Over the past decade, the growing body of research on TDP-43 pathology has led to considering TDP-43 as a potential major contributor to the neurodegenerative process. TDP-43’s normal function is essential for neuronal survival and the regulation of RNA processing and cellular stress response; abnormal TDP-43 protein leads to altered cell function and survival. TDP-43 is notably the neuropathological hallmark of amyotrophic lateral sclerosis (ALS) as well as some form of frontotemporolobar degeneration (FTLD). Tauopathies, divided in primary or secondary tauopathies cover other forms of FTLD including Pick disease (PiD), corticobasal degeneration (CBD), progressive supranuclear palsy (PSP) but also non-FTLD diseases like Alzheimer’s disease (AD) which can be classified as secondary tauopathy. As the importance of copathology is more and more recognized, TDP-43 is also frequently observed in conjunction with other proteinopathies, possibly with a synergistic or additive effect, although the exact mechanism is still unclear. In Alzheimer’s disease, the limbic predominant age-related TDP-43 encephalopathy neuropathologic change (LATE-NC) co-occurrence with Alzheimer’s disease neuropathologic changes (ADNC) lead to a more rapid course. Although there are currently no approved and validated biomarkers for its early detection, several promising tools, including neuroimaging and biofluid biomarkers, are under development, offering hope for the earlier detection of TDP-43 pathology in vivo. Accurate identification of the underlying proteinopathies and pathological processes could lead to better diagnosis and classification, more precise selection of clinical trial candidates, and ultimately, disease-specific tailored treatments.